Encyclopedia of Cognitive Science 2006
DOI: 10.1002/0470018860.s00187
|View full text |Cite
|
Sign up to set email alerts
|

Change Blindness

Abstract: Change blindness is a phenomenon in visual perception in which very large changes occurring in full view in a visual scene are not noticed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Despite making many similar predictions for behavior, this modified slot model remains fundamentally different from the resource model and has radically different implications for how the brain solves the problem of storing visual information. Understanding the nature of visual short term memory is crucial to understanding how observers perceive the world (Simons and Rensink, 2005; O’Regan, 2001), deploy attention to visual items (Bundesen and Habekost, 2008; Awh and Jonides, 2001; de Fockert et al, 2001; Lepsien and Nobre, 2007; Soto and Humphreys, 2006) or dynamically acquire information about a scene from glimpses obtained between eye movements (Irwin, 1991; Henderson, 2008). The color report task provides a key paradigm to consider and test these opposing views.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite making many similar predictions for behavior, this modified slot model remains fundamentally different from the resource model and has radically different implications for how the brain solves the problem of storing visual information. Understanding the nature of visual short term memory is crucial to understanding how observers perceive the world (Simons and Rensink, 2005; O’Regan, 2001), deploy attention to visual items (Bundesen and Habekost, 2008; Awh and Jonides, 2001; de Fockert et al, 2001; Lepsien and Nobre, 2007; Soto and Humphreys, 2006) or dynamically acquire information about a scene from glimpses obtained between eye movements (Irwin, 1991; Henderson, 2008). The color report task provides a key paradigm to consider and test these opposing views.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the nature of visual working memory – sometimes referred to as visual short term memory (VSTM) – is fundamental to understanding aspects of visual perception (Simons and Rensink, 2005; O’Regan, 2001), attention (Bundesen and Habekost, 2008; Awh and Jonides, 2001; de Fockert et al, 2001; Lepsien and Nobre, 2007; Soto and Humphreys, 2006) and integration of visual information across eye movements (Irwin, 1991; Henderson, 2008). Deficits in visual working memory have also been linked to damage to parietal and frontal brain regions, and are associated with disorders of visual perception and attention (D’Esposito and Postle, 1999; Logie and Della Sala, 2005; Mannan et al, 2005; Müller and Knight, 2006).…”
mentioning
confidence: 99%
“…However, what is noted in a scene is influenced by both exogenous (i.e., perceptual or stimulus-driven) factors, such as salience, and voluntary endogenous (i.e., cognitively or goal-driven) higher level factors, such as meaningfulness (Egeth & Yantis, 1997;Klein, Kingstone, & Pontefract, 1992;Theeuwes, 1994). Some researchers have concluded that centrality is primarily a function of exogenous factors such as object salience (Pringle, Irwin, Kramer, & Atchley, 2001;Shore & Klein, 2000); whereas others have concluded that centrality is a function of endogenous orienting of attentional processes (Agostinelli, Sherman, Fazio, & Hearst, 1986;Hollingworth & Henderson, 2000;Pringle et al, 2001;Shore & Klein, 2000) based on the meaning or gist of the scene (O'Regan, 2003). However, no previous study has manipulated explicitly both endogenous and exogenous factors within a single experiment.…”
mentioning
confidence: 99%
“…Change blindness refers to the failure to see large changes in objects and scenes when the changes are gradual [26] or happen during a visual disruption [27][28][29][30]. Studies in laboratory and real-world settings have found that people regularly fail to detect visual changes that take place within their field of view [27][28][29][30][31]. According to Rensink [30], change detection is the apprehension of change in the world around us, "it denotes not only proper detection (reporting on the existence of the change), but also identification (reporting what the change is) and localization (reporting where it is)" (p. 246).…”
Section: Change Blindnessmentioning
confidence: 99%
“…Many researchers agree that focused attention is needed to see change [29,32,33]. Visual transients -detectable visual cues that signal a change in the environment over time-such as colour, flashing, highlighting, boxing, and motion have been well studied as cues to capture attention in visual displays [34][35][36], however the efficiency of those cues varies between situations.…”
Section: Change Blindnessmentioning
confidence: 99%